Identifier Bouffants: An Exploration of the Impact on Verbal Communication Among Interdisciplinary Operating Room Personnel. - Grogan, Megan (AANA Journal, 2022)
Effective team communication reduces errors in the perioperative environment and is an essential component of patient safety. Although name and title recognition are beneficial in enhancing communication, often members of the interdisciplinary team are unfamiliar with their colleagues. This lack of familiarity is worsened when the visual cue of a name badge is obscured under sterile scrub attire. The primary purpose of this quasi-experimental study was to explore whether or not the use of identifier bouffants, which provided a visual cue of the anesthesia provider's name and position on their forehead, impacted verbal communication and familiarity within the operating room team. Participation in this study was voluntary and data were collected using a twenty-five question Likert-Scale survey. A significant association was identified between the presence of an identifier bouffant in the operating room and self-reported increased communication amongst the interdisciplinary operating room team (z = 5.42, P <.001). Of the 72 participants meeting inclusion criteria, 59 (82%) agreed that verbal communication was enhanced by the use of identifier bouffants in the operating room. Further exploration of strategies to improve name and title recognition in the operating room setting are supported by the results of this study.